Handbook of global economic policy - Nagel, Stuart S., 1934- (New York : Marcel Dekker, 2000)
A handbook of global economic policy. It develops practical, non-ideological solutions to the problems, and tests its solution's feasibility through economic, administrative, political, psychological, legal, international and technological obstacles.
Preface; Contents; Contributors; INTRODUCTION; Environmental Policy in the African Development Bank and the Asian Development Bank; Reforming Transport with Dominant State-Owned Enterprises; From Conflict to Order? Corporatism in South Africa; International Financial Institutions and the Politics of Structural Adjustment; Mechanisms for Labor Harmony Dispute Resolution in the Industrial Courts of Kenya and Zambia; Industrial Policy and Regional Development A Diachronic Comparison of Japanese and South Korean Economic Strategies.
Includes index.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Economic policy -- Case studies; Environmental policy -- Economic aspects -- Case studies; Labor policy -- Case studies; Full employment policies -- Case studies; Industrial policy -- Case studies; Post-communism -- Case studies; Policy sciences -- Case studies; Politique économique -- Études de cas; Environnement -- Politique gouvernementale -- Aspect économique -- Études de cas; Travail -- Politique gouvernementale -- Études de cas; Plein emploi -- Études de cas; Politique industrielle -- Études de cas; Postcommunisme -- Études de cas; Sciences de la politique -- Études de cas; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic policy; Environmental policy -- Economic aspects; Full employment policies; Industrial policy; Labor policy; Policy sciences; Post-communism; Electronic books; Case studies; Case studies; Études de cas